Late Quaternary palaeochannels in the distal area of the Salado-Juramento fluvial megafan, South America (Latin American Journal of Sedimentology and Basin Analysis, 2024)
The Gran Chaco fluvial systems, South America, constitute a significant type of fluvial record for the modern Andean foreland basin. The Salado-Juramento fluvial megafan (SJFM), one of the largest systems of South America, shows distinctive morphologic and sedimentologic characteristics. The SJFM, developed after the southward Salado-Juramento river displacement, shows numerous paleochannels with an eastward distributive pattern from its apex in the Sierras Subandinas. In this work, we analyze the palaeohydrological attributes and the sedimentology of two paleochannel sections located in distal areas of the SJFM, with the aim to collect stratigraphic and sedimentologic data to infer the dynamics of infill of those paleochannels. From each succession, sediment samples for sedimentologic (mineralogy and grain size) and chronologic analyses were taken. The paleochannels with-to-thickness ratio (W/T) show values between 9.4 and 16.1 (mean 12.75) for the distal area of the SJFM, corresponding to ribbon channels. The paleochannel infill is composed of very fine to fine sand, with a sand and clay composition related to the Salado River. These deposits are covered by layers of eolian clayed silt deposits. The geomorphology, paleohydrologic attributes, sedimentology, and numerical datings suggest a distributive paleodrainage with channels active during the MIS 3 (62-28 Ka BP). A fluvial aggradational phase is interpreted for the MIS 3, mainly represented by sinuous channels infill suggesting numerous divergent rivers in the distal SJFM. By the MIS 2, the activity of the fluvial system diminishes being replaced by clayed silt eolian sedimentation.
Keywords: Palaeochannels; Chaco Fluvial Megafan; Quaternary; Fluvial Dynamics; Channel Fill